Optimisation of gate‐commutated thyristors for hybrid DC breakers. Issue 14 (18th September 2017) - Lyu, Gang; Yu, Zhanqing; Zeng, Rong; Liu, Jiapeng; Zhang, Xueqiang; Long, Teng; Palmer, Patrick
Abstract : Hybrid DC breakers (HCBs) are crucial components in modern DC systems. Integrated gate‐commutated thyristors (IGCTs) are widely used in high‐voltage HCBs due to their controllable turn‐off capabilities under high‐power conditions. The focus of this study is on the optimisation of gate‐commutated thyristors (GCTs) for HCB applications, including operation temperature and design parameters. The considerations of GCT design and operating conditions for the use in HCBs are discussed. Under those considerations, a 2D finite element model of GCT is developed to investigate the influence of the GCT design parameters on the maximum controllable current (MCC) and the safe operation area (SOA). Impedance unevenly distributed along the full wafer has been calculated to obtain accurate simulation results. Results show that the P + ‐base, lifetime, and the distance between cathode and gate metallisation can all affect the MCC. In addition, GCTs can provide a higher MCC by operating at a higher temperature.